Predictive control of AC/AC matrix converter - Yusoff, Siti Hajar; Midi, Nur Shahida; Khan, Sheroz; Tohtayong, Majdee (Institute of Advanced Engineering and Science (IAES), 2017)
This work investigates the usage of Model Predictive Control (MPC) for a three phase conventional matrix converter with low pass filter at the input and output side. The conventional matrix converter has 3 input and 3 output which gives 27 switching state. From this design, a MPC is incorporate to control the output voltage and the input currents for all the phases. The design of the proposed controller is based on the input current controller and output voltage controller with load observer. The proposed MPC using cost function will select the minimized switching state to be applied to next switching. This gives a sinusoidal output voltages and input currents. A simulation and experimental studies are presented to validate the proposed control scheme.